2004
DOI: 10.1002/ejic.200300576
|View full text |Cite
|
Sign up to set email alerts
|

Novel Thiotetraazapentalene Complexes from the Reaction of a Ruthenium Azide Complex with Alkyl Isothiocyanates

Abstract: Reactions of the ruthenium azide complex 1 with alkyl isothiocyanates give novel ruthenium thiotetraazapentalenedithione complexes 3a−c containing a hypervalent sulfur atom. The ligand, bound through one sulfur atom, is derived from three isothiocyanate molecules and one nitrogen atom from an azide ion. The synthesis and structural determination of 3a−c, as well as a possible mechanism for their formation is described. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 31 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Thiocyanates are ligands well-known to form MSCNM‘ bridges. A large number of complexes have been previously reported in which one of the metal centers being bridged is mercury. In contrast, more limited literature is available when one of the metal centers is ruthenium.
3 Molecular structure of the N719 − HgCl 2 complex showing (a) the asymmetric unit which contains one mercury atom, crystallographically disordered in two positions at half-occupancy, one [Ru(N 2 C 12 O 4 H 8 ) 2 (NCS) 2 ] complex, and two Cl - anions (disordered atoms from the carboxylic units and H atoms have been omitted for clarity) and (b) a representation of the structure of the [Ru(N 2 C 12 O 4 H 8 ) 2 (NCS) 2 HgCl] n n + chains parallel to the a axis.
…”
Section: Resultsmentioning
confidence: 99%
“…Thiocyanates are ligands well-known to form MSCNM‘ bridges. A large number of complexes have been previously reported in which one of the metal centers being bridged is mercury. In contrast, more limited literature is available when one of the metal centers is ruthenium.
3 Molecular structure of the N719 − HgCl 2 complex showing (a) the asymmetric unit which contains one mercury atom, crystallographically disordered in two positions at half-occupancy, one [Ru(N 2 C 12 O 4 H 8 ) 2 (NCS) 2 ] complex, and two Cl - anions (disordered atoms from the carboxylic units and H atoms have been omitted for clarity) and (b) a representation of the structure of the [Ru(N 2 C 12 O 4 H 8 ) 2 (NCS) 2 HgCl] n n + chains parallel to the a axis.
…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported by several researchers have shown that N - (or S -) coordinated tetrazole–thiolates are formed through dipolar cycloaddition reactions of main-group or transition-metal azido complexes with unsaturated organic compounds, such as R–NCS, R–SCN, and CS 2 . 1,2,10–17 In addition, metathesis reactions involving late-transition-metal halides and alkali-metal tetrazolates are known to afford S - or N -coordinated tetrazolato complexes of transition metals. 18,19 Some late transition-metal tetrazole–thiolates have been synthesized by the deprotonation of organic tetrazole–thiones in the presence of amines, NaOH, or metal acetates.…”
Section: Introductionmentioning
confidence: 99%